JIRIRI 2020
DOI: 10.33921/zfhp7561
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Sexual Assault: Effects of Victim Physiological Arousal and Victim Gender on Jurors’ Decisions

Abstract: Limited research has assessed juror decision making in cases of female perpetrated sexual assault and the role played by factors such as the victim’s gender, physiological arousal, and participant’s gender in the decision making process. Participants (n = 215) were presented with one of four trial vignettes that varied the perpetrator and victim’s gender and victim’s physiological arousal. The impact of these variables was examined on guilty verdicts rendered, credibility, and blameworthiness of the victim and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
2
11
1
Order By: Relevance
“…These findings match previous research which has consistently found male participants to indicate higher endorsement of rape myths (e.g. Davies et al, 2012;Gerger et al, 2007;Hammond et al, 2011;Hantzi et al, 2015;Johnson et al, 1997;Margolin et al, 1989;Mégias et al, 2011;Reilly et al, 1992;Rollero & Tartaglia, 2018;Starosta & Schuller, 2020;Watson, 2016;see Suarez & Gadalla, 2010 for a meta-analysis). This consistent difference between men and women may be a result of patriarchal structures of the societies in which the research was conducted.…”
Section: Associations Between Ammsa and Demographic Variablessupporting
confidence: 89%
“…These findings match previous research which has consistently found male participants to indicate higher endorsement of rape myths (e.g. Davies et al, 2012;Gerger et al, 2007;Hammond et al, 2011;Hantzi et al, 2015;Johnson et al, 1997;Margolin et al, 1989;Mégias et al, 2011;Reilly et al, 1992;Rollero & Tartaglia, 2018;Starosta & Schuller, 2020;Watson, 2016;see Suarez & Gadalla, 2010 for a meta-analysis). This consistent difference between men and women may be a result of patriarchal structures of the societies in which the research was conducted.…”
Section: Associations Between Ammsa and Demographic Variablessupporting
confidence: 89%
“…Of importance, the male complainant in every condition was blamed significantly more than his female complainant counterpart (Anderson, 2007;Pica et al, 2018;Starosta & Schuller, 2020). Similarly, the female defendant was viewed as significantly more credible and less blameworthy than the male defendant regardless of the other conditions (Anderson, 2007;Pica et al, 2018;Starosta & Schuller, 2020). Interestingly, no significant differences were found between jurors' verdict decisions for a male or a female complainant within these studies.…”
Section: Female-on-male Sexual Assaultmentioning
confidence: 62%
“…Specifically, male complainants who knew their assailant, who did not resist the assault, and who were intoxicated at the time of their assault were blamed more than those who were assaulted by a stranger, actively resisted, and were sober. Of importance, the male complainant in every condition was blamed significantly more than his female complainant counterpart (Anderson, 2007;Pica et al, 2018;Starosta & Schuller, 2020). Similarly, the female defendant was viewed as significantly more credible and less blameworthy than the male defendant regardless of the other conditions (Anderson, 2007;Pica et al, 2018;Starosta & Schuller, 2020).…”
Section: Female-on-male Sexual Assaultmentioning
confidence: 97%
See 2 more Smart Citations